PREVALENCE OF DIABETES MELLITUS AND HYPERTENSION AMONG DENTAL PATIENTS - A HOSPITAL BASED STUDY - Ravichandran, Vigneshwaran; J. Sherlin, Herald; Chaudhary, Manjari (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes Mellitus and Hypertension are two chronic, non - communicable diseases with increasing incidence worldwide. DM and HT are interrelated diseases that strongly predispose an individual to cardiovascular diseases and other systemic diseases. Hence diabetes mellitus and hypertension are quite important in dental settings as may present as an emergency during dental treatment or may necessitate a modification in the patient’s management. The objective of this study is to determine the prevalence of coexistence of Diabetes mellitus and Hypertension among the group of dental outpatients of Saveetha dental college and to assess the relationship with other systemic conditions and dental problems. The data from 86, 000 patients visited Saveetha dental college during the time period of June 2019 to March 2020 were reviewed and the data of patients with medical history of coexisting Diabetes Mellitus and Hypertension were collected. The data of additional systemic diseases and the dental problems of such patients were also collected. The obtained data were entered in an excel sheet. Then the data were imported to statistical analysis software [SPSS] and analyzed for significance. Among 24,132 patients, 279 patients have coexisting prevalence of Diabetes mellitus and Hypertension. The predominant age group of the patients was 41 to 70 yrs [87 %]. The gender was predominantly Male [52 %]. 84 % of these patients were not having any added systemic illness. 8 % of these patients have myocardial infarction. The predominant dental complaint of these patients was pulpitis [41 %] followed by edentulousness 19%, dental caries 18% and periodontitis 13%. The diet status of these patients was predominantly non-veg [97 %]. Dentists should note that co-existence of Diabetes mellitus and hypertension in a dental patient was an index of increased morbidity and mortality and should always screen for these medical conditions.